2021
DOI: 10.47836/pjst.29.3.43
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vegetation covers for outdoor thermal improvement: A Case Study at Abubakar Tafawa Balewa University, Bauchi, Nigeria

Abstract: Frequent increases in temperature and related consequences have been the trending phenomenon for over ten decades, with a general rise of about 0.740C. This study evaluates the effects of different percentage covers of tree canopies for outdoor thermal improvement of campus areas in Bauchi, Nigeria. Firstly, the study involves on-site measurement of existing features on the site and the climatic conditions. Secondly, performing simulation for evaluation of the plant-surface-atmosphere interactions with Envi-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…FLUENT was used to simulate air turbulence in an ideal urban green space condition in Guangzhou (Feng and Chu, 2017). Previous studies using ENVI-met have found that outdoor thermal improvements in campus areas are related to the effects of different levels of tree canopy closure in Nigeria (Abdulkarim et al, 2021). Liu et al (2018) set up simulation experiments using ENVImet.…”
Section: Introductionmentioning
confidence: 99%
“…FLUENT was used to simulate air turbulence in an ideal urban green space condition in Guangzhou (Feng and Chu, 2017). Previous studies using ENVI-met have found that outdoor thermal improvements in campus areas are related to the effects of different levels of tree canopy closure in Nigeria (Abdulkarim et al, 2021). Liu et al (2018) set up simulation experiments using ENVImet.…”
Section: Introductionmentioning
confidence: 99%
“…Increased tree canopy coverage effectively reduced air temperature and mean radiant temperature in urban residence, with air temperature and mean radiant temperature with high tree canopy coverage reduced by 3.3 • C and 13.9 • C, respectively, compared to urban residence with no tree canopy coverage [23]. A study in Nigeria showed that outdoor air temperature could be reduced by up to 3.38 • C and mean radiant temperature by up to 24.24 • C when 45 percent of the canopy was covered with trees [24]. Based on the consideration of thermal dynamics and human thermal comfort, the study quantified the maximum effective canopy cover thresholds of 45 percent, 30 percent, and 25 percent for residential areas of 33 m (11 floors), Forests 2024, 15, 518 3 of 23 54 m (18 floors), and 100 m (33 floors) in height, respectively [25].…”
Section: Current Research Perspectives On Greenery In Residential Areasmentioning
confidence: 99%